A new species of Passiflora (Passifloraceae, subgenus Passiflora) in the flora of Colombia discovered in uncharted Andean territory - Arrigui-Torres, Edwin; Ocampo, John A.; Rosero-Toro, Jeison Herley (Phytotaxa, 2024)
A new species of Passiflora belonging to the subgenus Passiflora (supersection Stipulata, section Kermesinae) is described and illustrated from living material and herbarium specimens. Passiflora pitalensis is similar to P. lehmannii, and it can be recognized primarily by its petiole green, leaves with broader lobes, peduncle green, bract lanceolate, corona filaments in 5 series with outer filaments in 2 series, fruit ovoid, and seed margin dentate. This species is rare and endemic to Colombia in the Andean region at elevations ranging from 1,749–2,027 m and should be considered Endangered (EN) due to its restricted occurrence with a small population size of no more than 90 individuals.